Aza-BODIPY-Based Bifunctional Photocatalyst for Red-Light-Driven Asymmetric Hydroxylation of β‑Ketoesters - Guo, Yonghong; Zhao, Jiayi; Zu, Bing; He, Chuan (Synthesis, 2024)
A novel bifunctional photocatalyst combining an aza-BODIPY and a chiral oxazoline has been developed. This photocatalyst enables the asymmetric hydroxylation of β‑ketoesters under an oxygen atmosphere and irradiation with 18-W red LEDs. This procedure offers a convenient and potentially general approach to obtain enantioenriched α-hydroxy-β-dicarbonyl products. The results reported in this manuscript demonstrate the promise of this new organic photocatalyst design and will help expand the application of BODIPY-based chiral photocatalysts.
Keywords: bifunctional photocatalyst; aza-BODIPY; asymmetric catalysis; β‑ketoesters; red-light photocatalysis